The Application of Organizational Culture in Establishing a Performance Based Bureaucracy at the BKPSDM of Kuningan Regency - Rima Ismatul Muhibbah; Leni Rohida (International Journal Labs, 2026)
Organizational culture plays a crucial role in shaping the work behavior and performance of State Civil Apparatus (ASN) within government agencies. Organizational culture is a determining factor in fostering professionalism, discipline, and the quality of public service. This study aimed to analyze organizational culture and its implications for ASN performance at the Kuningan Regency Civil Service and Human Resources Development Agency (BKPSDM) using Edgar H. Schein's organizational culture theory perspective. This study employed a qualitative approach with a case study method. The results indicate that organizational culture at the Kuningan Regency BKPSDM has been implemented at three levels. At the artifact level, the implementation of SOPs, the use of application-based work systems, and the support of work facilities are forms of organizational culture that can be directly observed. At the adopted level, the implementation of ASN BerAKHLAK core values plays a role in shaping ASN professionalism, discipline, cooperation, and service orientation. At the basic assumption level, communicative and development-oriented leadership patterns shape work habits that emphasize punctuality and openness to innovation. Overall, this study concludes that the organizational culture at the Kuningan Regency Human Resources Development Agency (BKPSDM) has been functioning quite well, but has not yet fully optimized the performance of civil servants (ASN). Therefore, strengthening the organizational culture is necessary.